Impact of Supply Chain Management On The Market Value Of The Company Using The Discounted Cash Flow Method - Miguel, Diaz; Lyzhova, Anna (International Journal of Supply Chain Management, 2020)
Abstract- The purpose of this research is to study the impact of the supply chain that determine the financial sustainability of an organization on its market value. The analysis considers that in the process of determining the value of an organization through the use of the discounted cash flow method, a series of supply chain factors that reflect its financial sustainability are not taken into account and consequently, have a strong impact on the market value. The research has carried out a correlation study based on empirical data and has examined one of the most used valuation methods. Considering the relationship between supply chain management and the market value of an organization, it is intended to present scientific evidence to determine that the discounted cash flow model has certain shortcomings in the valuation process of an entity that reflect the lack of supply chain when this method is used.